Circulating adhesion molecules in sarcoidosis. - Hamblin, A S (1994)
Sarcoidosis is a disease of unknown etiology characterized by non-caseating granulomata together with a number of systemic abnormalities. We have recently shown these include increased expression of the integrins CD11/CD18 on peripheral blood leucocytes. Here we have measured serum levels of the adhesion molecules intercellular adhesion molecule-1 (ICAM-1), E-selectin and vascular cell adhesion molecule-1 (VCAM-1) in 23 patients and 14 normal controls using antigen capture sandwich ELISAs. Median circulating E-selectin levels in the patients were nearly three times those of the controls (P < 0.0001, Mann-Whitney U-test), whilst ICAM-1 but not VCAM-1 levels were only slightly elevated. These results show that endothelial cell activation and shedding of E-selectin into the circulation are additional features of the pathology of sarcoidosis.